The Influence of Coupled Thermomechanical Processes on the Pressure and Temperature due to Cold Water Injection into Multiple Fracture Zones in Deep Rock Formation. (6th January 2020) - Figueiredo, Bruno; Tsang, Chin-Fu; Niemi, Auli
Abstract : A technique to produce geothermal energy from deep rock formations at elevated temperatures consists of drilling two parallel deep boreholes, the second of which is directed so as to intersect a series of fractures produced by hydraulic fracturing in the first borehole. Then, the first borehole is used for injection of cold water and the second used to produce water that has been heated by the deep rock formation. Some very useful analytical solutions have been applied for a quick estimate of the water outlet temperature and injection/production pressures in this enhanced geothermal system (EGS), but they do not take into account the influence of thermomechanical and hydromechanical effects on the time evolutions of the pressure and temperature. This paper provided help for the engineering design of the EGS based on these analytical solutions, by evaluating the separate influences of the thermal (T), hydromechanical (HM), thermo-hydro-mechanical (THM) effects on the fluid pore pressure and temperature. A thermo-hydro-mechanical (THM) model was developed to simulate the heat extraction from multiple preexisting fracture zones in the hot rock formation, by considering permeability changes due to the injection pressure as a function of changes in the mean effective stress. It was found that the thermal effects (without coupling with mechanical effects) led to a decrease of the transmissivity of the fracture zones and a consequent increase in the injection pressure, by a maximum factor of 2. When the temperature is constant, the influence of the hydromechanical effects on the fluid pore pressure was found to be negligible, because in such scenario, the variation of the mean effective stress was 3 MPa, which was associated with a maximum increase in the initial permeability of the fracture zone only by a factor of 1.2. Thermo-hydro-mechanical effects led to a maximum increase in the permeability of the fracture zones of approximately 10 times the initial value, which was associated with a decrease in the fluid pore pressure by a maximum factor of 1.25 and 2, when hydrological and thermohydrological effects were considered, respectively. Changes in temperature were found not to be affected significantly by the thermomechanical and hydromechanical effects, but by the flow rate in the fracture zones. A sensitivity analysis was conducted to study the influence of the number, the initial permeability, the elastic modulus and the residual porosity of the fracture zones, and the elastic modulus of the confining intact rock, on the simulation results. The results were found to be the most sensitive to the number and the initial permeability of the fracture zones.